Pengaruh Kepercayaan dan Mutu Pelayanan terhadap Kepatuhan Imunisasi Dasar Lengkap di Sekanak Raya - Geda Lilova Maja Nanda; Nelli Roza; Huzaima Huzaima (Pusat riset dan Inovasi Nasional, 2025)
Background: In 2021, there were 38 deaths for every 1000 live births in the world's under-five population. Predisposing factors, enabling resources, need, and health service usage are the three primary elements that make up Andersen's theory and have an impact on health care utilisation. Goal: To ascertain how patient trust and service quality relate to Sekanak Raya Village's whole basic immunisation program. Method: This study is quantitative in nature and uses a cross-sectional, analytical observational methodology. The mothers who had children in Sekanak Raya Village made up the study's population. Tools for gathering data include questionnaires and observation sheets. In data analysis, the chi-square test was employed. Result: The findings indicate that 15 out of 100 underdog moms believe in complete basic immunisation status, whereas 18 out of 100 underdog mothers believe that the quality of service is good with complete basic immunisation status. For patient confidence, the chi square statistical test yielded a p-value of 0.022 < 0.05, whereas for service quality, the p-value was 0.004 < 0.05. In Sekanak Raya Village, UPTD Working Area, Puskesmas, Rear Padang, Batam City, total basic immunisation quality and patient trust are significantly correlated in 2024.